Membangun Jiwa Usaha Melalui Pelatihan Kewirausahaan - Mukrodi Mukrodi; Wahyudi Wahyudi; Endang Sugiarti; Tri Wartono; Martono Martono (Jurnal PKM Manajemen Bisnis, 2021)
The best of humans is beneficial to others. Trying to contribute to their abilities, both in the field of knowledge, energy, or material. This information is attached to an educator. As knowledgeable people, educators are required to educate and advance community life. Therefore, service activities are carried out, as evidence of the contribution of educators. Realistically, this activity is carried out using qualitative techniques. The service is carried out by direct interaction through discussion and practice. Participants in the activity were residents of the Reni Jaya housing complex, especially teenagers. Based on the results of the activity, a conclusion can be drawn, in general the participants are interested in entrepreneurship, but limited knowledge, experience, and costs become obstacles.